Faktor-faktor yang Berhubungan dengan Perilaku Higiene Penjamah Makanan pada Pangan Industri Rumah Tangga di Kecamatan Geragai Tahun 2022 - isabella josita baringbing; Willia Novita Eka Rini; Fitria Eka Putri (Jurnal Kesmas Jambi, 2023)
Food sanitation hygiene is an effort to control the risk factors for contamination of food, both originating from food ingredients, people, places and equipment so that it is safe for consumption. Based on the East Tanjung Jabung Health profile, in the Simpang Padan Health Center work area it is known that there are still many Food Processing Places that do not meet the requirements, namely as much as 85.4%. This research is an analytic observational study with a cross sectional approach. This research was conducted on Home Industry Food (PIRT) in Geragai District. The research population was all PIRT food handlers. The research sample is 51 people, with total sampling technique. The results of this study indicate that knowledge (p = 0.008), attitude (p = 0.033) have a relationship with food handler hygiene behavior. While the level of education (p = 1.000) and food safety counseling (p = 0.934) had no relationship with food handler hygiene behavior. Knowledge, attitude and level of education are factors that greatly influence the hygiene behavior of food handlers. It is hoped that food handlers can increase their knowledge and attitudes by participating in counseling or training organized by related agencies.